2022
DOI: 10.3390/antiox11020342
|View full text |Cite
|
Sign up to set email alerts
|

H2O2/Ca2+/Zn2+ Complex Can Be Considered a “Collaborative Sensor” of the Mitochondrial Capacity?

Abstract: In order to maintain a state of well-being, the cell needs a functional control center that allows it to respond to changes in the internal and surrounding environments and, at the same time, carry out the necessary metabolic functions. In this review, we identify the mitochondrion as such an “agora”, in which three main messengers are able to collaborate and activate adaptive response mechanisms. Such response generators, which we have identified as H2O2, Ca2+, and Zn2+, are capable of “reading” the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In particular, Zn 2+ -associated signalling pathways are involved in the development of diabetic cardiomyopathy and other heart diseases [6,7]. In that regard, the close coordination of [Ca 2+ ] i and [Zn 2+ ] i homeostasis in mitochondrion balances the redox status and oxidative stress status of cardiomyocytes and provides a cardioprotective effect [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zn 2+ -associated signalling pathways are involved in the development of diabetic cardiomyopathy and other heart diseases [6,7]. In that regard, the close coordination of [Ca 2+ ] i and [Zn 2+ ] i homeostasis in mitochondrion balances the redox status and oxidative stress status of cardiomyocytes and provides a cardioprotective effect [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the age-dependent increase in oxidative damage in muscle of healthy subjects may reflect either increased free radical production or insufficient activity of scavenger/repair systems. 57 Histological and molecular data on skeletal muscle from Long-COVID patients are currently very limited. They are mainly based on case reports and are insufficient to define an established hypothesis.…”
Section: Oxidative Stress In Skeletal Muscle Of Long-covid Patientsmentioning
confidence: 99%
“…It is known that Zn 2+ -associated signalling pathways are involved in the development of diabetic cardiomyopathy and other heart diseases. Mitochondria coordinate [Ca 2+ ] i and [Zn 2+ ] i homeostasis, which affect cellular ROS production, mitochondria ultrastructure and efficiency [106,107]. The role of Zn 2+ homeostasis in DM and obesity-induced cardiac remodelling, inflammation, dysfunction and other cardiovascular diseases and complications was covered in several recent reviews [108][109][110].…”
Section: Zinc Supplementation In Dm Treatment and Cardioprotectionmentioning
confidence: 99%